2020
DOI: 10.1186/s12989-020-00353-3
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles induce lung inflammation in mice via ROS/PARP/TRPM2 signaling-mediated lysosome impairment and autophagy dysfunction

Abstract: Background: Wide applications of nanoparticles (NPs) have raised increasing concerns about safety to humans. Oxidative stress and inflammation are extensively investigated as mechanisms for NPs-induced toxicity. Autophagy and lysosomal dysfunction are emerging molecular mechanisms. Inhalation is one of the main pathways of exposing humans to NPs, which has been reported to induce severe pulmonary inflammation. However, the underlying mechanisms and, more specifically, the interplays of above-mentioned mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 76 publications
(99 reference statements)
2
49
0
Order By: Relevance
“…Other studies in the past, including some of our investigations, proposed a mechanism of silica toxicity based on particleassociated radicals (e.g., silyl, siloxyl radicals) and ROS (e.g., hydroxyl, superoxide, and peroxyl radicals), the latter originating from the reaction with atmospheric components of dangling bonds upon fracture/grinding of the particles (64,65) or opening of strained three-membered siloxane rings (30). In some proinflammatory and profibrogenic cell-signaling pathways and transcription factor activation, the triggering role of particle ROS cannot be disregarded (66)(67)(68)(69), and they can contribute to increasing the oxidative stress in the lung milieu (20). The present data clearly document that particle ROS are not critical for membrane damage initiated by silica particles, as also shown in previous studies (45,(70)(71)(72).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in the past, including some of our investigations, proposed a mechanism of silica toxicity based on particleassociated radicals (e.g., silyl, siloxyl radicals) and ROS (e.g., hydroxyl, superoxide, and peroxyl radicals), the latter originating from the reaction with atmospheric components of dangling bonds upon fracture/grinding of the particles (64,65) or opening of strained three-membered siloxane rings (30). In some proinflammatory and profibrogenic cell-signaling pathways and transcription factor activation, the triggering role of particle ROS cannot be disregarded (66)(67)(68)(69), and they can contribute to increasing the oxidative stress in the lung milieu (20). The present data clearly document that particle ROS are not critical for membrane damage initiated by silica particles, as also shown in previous studies (45,(70)(71)(72).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, the activity of nuclear PARP, particularly PARP-1, is crucial for the induction of ADPR generation and subsequent TRPM2 channel activation by ROS and other OS-inducing pathological stimuli. PARP inhibitors have been used in many studies as an alternative or additional means to prevent OS-induced TRPM2-mediated effects [ 36 , 39 , 48 , 74 , 75 , 82 , [121] , [122] , [123] , [124] , [125] , [126] ], including cell death. Example PARP inhibitors include SB-750139, N-(6-oxo-5,6-dihydro-phenanthridin-2-yl)-N,N-dimethylacetamide (PJ34), 3-aminobenzamide (3-AB) and 3,4-dihydro-5-[4-(1-piperidinyl)butoxy]-1(2H)-isoquinolinone (DPQ).…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…It is known that ER stress is an important indicator of pericyte dysfunction that can itself potentiate cellular damage and induce cell death via autophagy [ 157 , 158 ]. Increasing evidence suggests that ultrafine PMs with a size of <100 nm commonly present in polluted air and diverse NPs widely used in nanomaterials are potent in inducing OS [ 13 , 48 ], ER stress and autophagy-mediated cell death [ 159 , 160 ]. We have recently examined the role of the TRPM2 channel in mediating zinc oxide-NPs (ZnO-NPs)-induced OS, ER stress and autophagy in brain vascular pericytes [ 161 ].…”
Section: Trpm2 In Pericyte Death Associated With Neurovascular Functimentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies on the safety in human, reproducibility, stability and scalability of the silica nanoparticles are expected. Numerous studies reported the toxicity profiles of silica nanoparticles in vitro cells or animal models [140][141][142][143][144][145]. However, to date, only one study confirmed that silica nanoparticles are safe in healthy humans [129].…”
Section: Potential For Future Researchmentioning
confidence: 99%